Analysis Of The Quality Of Delivery And Students’ Engagement In Universiti Sains Malaysia-Developed Video Lectures - Naeini, Fatemeh Habibian (2018)
In an effort to transform teaching and learning in the university, Universiti Sains Malaysia (USM) has embarked on providing recorded video lectures on its own official Learning Management System. The measure of the Quality of Delivery of video lectures is captured by the Direct Instruction model of teaching, where the instructor acts as a content expert who directly engages the learners and at the same time manages their learning. The lecturers are evaluated by their students at the end of the semester, but there is no evaluation as to whether their lectures have followed the Direct Instruction format.